Translated hypermodality: A descriptive analysis of translation-related electronic material. Issue 2 (26th August 2015) - Calzada-Perez, Maria
Abstract : The present paper revolves around the notions of hypermodality and translation under the current globalizing scenario. The first section of the paper presents a basic framework of analysis devised within multimodal/hypertextual paradigms, drawing mainly on Kress and Van Leeuwen (1996), Lemke (2002), Lim (2004), Cheong (2002), Askehave and Nielsen (2004), among others. The second section applies this framework to the study of electronic 'translational material'. Thus, section 2 is devoted to a set of webpages devised by Procter and Gamble, which play the role of new electronic forms of advertising. These webpages result from a combination of different kinds of translational processes which are discussed at some length with the help of the hypermodal framework proposed earlier. In short, the present paper places itself in the midst of our current globalized (i.e. dematerialized) environment – where technical advances result in new textual typologies, where there is an increasing exchange of translation material and where cross cultural hypermodality simply cannot be avoided.